Numerical analysis on static load capacity of prestressed concrete sleepers under hypothetical bearing pressure distribution - Wan Azlan Wan Abdul Rashid, 1986- (2012)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2012